Acupoint stimulation methods for premature ovarian insufficiency: a systematic review and network meta-analysis of randomized controlled trials - Du, Zhenping; Ye, Guancheng; Wei, Jingyuan; Li, Shutong; Zhao, Shan; Wang, Jun (Frontiers in Endocrinology, 2025)
ObjectiveThe aims of this study were to evaluate and rank the efficacy of different acupoint stimulation (AS) therapies in the treatment of premature ovarian insufficiency (POI) by network meta-analysis (NMA) and to explore the optimal AS regimen for improving sex hormone levels and clinical symptoms.MethodsRandomized controlled trials (RCTs) in English and Chinese up to November 2024 were searched in eight databases, including the Cochrane Library, PubMed, and the China National Knowledge Infrastructure (CNKI). Included studies were patients with POI diagnosed according to established international or Chinese guidelines. The intervention compared AS therapies (e.g., acupuncture, moxibustion, and electroacupuncture) with conventional treatments (oral herbs or hormone replacement therapy) or/and placebo. Outcome indicators included antral follicle count (AFC), follicle-stimulating hormone (FSH) levels, luteinizing hormone (LH) levels, estradiol (E2) levels, and Kupperman scores. The outcome indicators were evaluated on days 2–5 of the menstrual period. Exclusion criteria included non-RCTs, duplicate publications, non-peer-reviewed literature, studies with unclear outcome/baseline data, studies with a non-POI diagnosis, studies with a before-and-after own-control design, non-human studies, and studies with missing continuous data. Literature quality and risk of bias were assessed using Review Manager (RevMan), Version 5.3. Statistical analysis was performed using Stata 16.0 software, mvmeta package, and surface under the cumulative ranking curve (SUCRA).ResultsA total of 51 RCTs were retrieved, including 3,754 patients. A methodological assessment of 51 RCTs revealed generalized risks: 9.8% of RCTs used incorrect randomization methods; 29% of RCTs did not describe explicit randomization; all RCTs did not have explicit allocation concealment; 98% of RCTs did not mention blinding; all RCTs reported complete outcome data; and 98% of RCTs had unclear risks. Therapies combining multiple AS therapies (especially moxibustion-related therapies) improved ovarian function significantly. Acupuncture combined with moxibustion (Acu + Moxi) was effective in increasing AFC [mean difference (MD) = 2.04, 95% confidence interval (CI) (1.31, 2.77); SUCRA = 75.1%]. Auricular seed therapy (AST) was most effective in reducing FSH [MD = 3.03, 95% CI (0.45, 5.60); SUCRA = 83.7%]. Acupuncture (Acu) was effective in reducing LH levels [MD = 1.52, 95% CI (0.27, 2.77); SUCRA = 58.3%]. Moxibustion combined with tuina (Moxi + MT) [MD = 11.92, 95% CI (8.19, 15.65); SUCRA = 100%] and moxibustion combined with acupressure [MD = 3.20, 95% CI (0.16, 6.24); SUCRA = 81.4%] significantly increased E2 levels. Moxibustion combined with tuina (Moxi + MT) had the best effect on Kupperman score improvement [MD = 4.63, 95% CI (0.58, 8.68); SUCRA = 92.1%]. Adverse events for all therapies involved in this study were mild and resolved with symptomatic management.ConclusionAS therapies (especially those combined with moxibustion) can safely and effectively improve hormone levels and clinical symptoms in patients with POI, supporting their clinical application as complementary and alternative medicine (CAM).Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024612169.